From Victims to Litigants - MacDowell, Elizabeth L. (2016)
This Article reports findings from an ethnographic study of self-help programs in two western states. The study investigated how self-help assistance provided by partnerships between courts and nongovernmental organizations implicates advocacy and access to justice for domestic violence survivors. The primary finding is that self-help programs may inadvertently work to curtail, rather than expand, advocacy resources. Furthermore, problems identified with self-help service delivery and negative impacts on advocacy systems may be explained by the structure of work within self-help programs and the nature of partnerships to provide self-help services. The Author uncovers previously unseen impacts of self-help programs on survivors and on the resources to help them. She concludes with a discussion of the implications for future research directions and describes what can be done now to improve self-help services for survivors